Acute retinal necrosis in a patient with remote severe herpes simplex encephalitis - Kobayashi, Takaaki (BMJ Case Rep, 2019)
A 60-year-old man with a history of severe herpes simplex virus type 1 (HSV-1) encephalitis 2 years prior presented with acute onset of visual loss in the left eye. Dilated funduscopic examination showed retinitis and occlusive vasculitis with retinal necrosis. PCR of the vitreous fluid was positive for HSV-1, and he was diagnosed with acute retinal necrosis (ARN) due to HSV-1. The patient was treated with intravenous acyclovir and intravitreous foscarnet for 2 weeks, followed by high dose oral valacyclovir for 2 weeks. He was subsequently placed on planned life-long suppressive valacyclovir. His case demonstrates that acute visual loss concomitant with or subsequent to HSV-1 encephalitis warrants suspicion of ARN. Prompt therapy with effective antiviral medication is necessary to reduce the risk of sight-threatening complications. Chronic suppression with oral antiviral therapy after ARN is recommended to prevent involvement of the contralateral eye, though there is no consensus on the duration and dosage of antivirals.